Antioxidant activity of Patanwadi breed sheep milk over cow milk— A preliminary study - HAZRA, TANMAY; G, SINDHAV ROHIT; BUMBADIYA, MITUL; GOVANI, RADHIKA; RAMANI, VIMAL M (The Indian Journal of Animal Sciences, 2025)
Milk is an excellent source of dietary antioxidants, however, the antioxidants activity of different species of milk varies significantly. Sheep milk’s compositional and functional properties are one of the untapped areas for Indian researchers. This present study evaluated and compared the antioxidant potential of Patanwadi breed sheep milk over cow milk. The protein, fat, and lactose content of Patanwadi breed sheep milk was significantly higher than cow’s milk. Different anti-oxidant assays confirmed that the antioxidant activity of sheep milk was superior to cow milk. The present study supports that Patanwadi breed sheep could be a potential source of dietary antioxidants. Therefore, more scientific studies are required to develop sheep milk functional dairy products, and thereof optimized process parameters for sheep milk dairy products in Indian conditions.